PENGARUH LATIHAN RENANG GAYA BEBAS JARAK 25 METER DAN 50 METER TERHADAP KECEPATAN RENANG GAYA BEBAS 100 METER USIA 15 TAHUN DI CLUB RENANG DURI LANTERA AQUATIC - Sebayang, Garsia Sangapta; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The aim of this research is to find out whether there is a jointinfluence on swimming training distances of 25 (twenty five) meters and 50 (fifty)meters on the freestyle swimming speed of 15 (fifteen) year olds at the Duri LamteraAquatic Swimming Club. This research refers to a quantitative research approach. Thesample that met the characteristics above was 7 people and then divided into twogroups using a group division technique using ordinal pairing. The research thatresulted in the final hypothesis was answered that swimming training distances of 25meters and 50 meters on the freestyle swimming speed of 15 year olds at the DuriLamtera Aquatic Swimming Club got a sig value. 2 tailets 0.761 and 0.086. That meansthere are differences in the training of the two.Keywords: Freestyle Swimming Training, Swimming Speed